1993
DOI: 10.1093/clind/16.6.750
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Outbreak Due to Enterococcus faecium Highly Resistant to Vancomycin, Penicillin, and Gentamicin

Abstract: In October 1990, Enterococcus faecium that was highly resistant to glycopeptides, penicillins, and aminoglycosides was isolated from the peritoneal dialysis fluid from a patient in an intensive care unit. Over the following 6 months, multiresistant E. faecium organisms were isolated from cultures of blood, urine, or surgical wound specimens from eight additional patients. Surveillance cultures of groin and/or rectal swabs were positive for eight of 37 patients and four of 62 employees at risk. Restriction endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
257
2
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(274 citation statements)
references
References 0 publications
8
257
2
4
Order By: Relevance
“…The most frequent risk factors found included vancomycin use, cephalosporin use, highacuity illness, and immunosuppression. [3][4][5][6] In our study of liver transplant recipients, some of these factors were also found. However, we also identified frequent biliary tract manipulation as a risk factor, suggesting that recipients with biliary complications were at a greater risk for invasive infection.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The most frequent risk factors found included vancomycin use, cephalosporin use, highacuity illness, and immunosuppression. [3][4][5][6] In our study of liver transplant recipients, some of these factors were also found. However, we also identified frequent biliary tract manipulation as a risk factor, suggesting that recipients with biliary complications were at a greater risk for invasive infection.…”
Section: Discussionsupporting
confidence: 64%
“…2 Other centers have identified several risk factors for VREF infection, including empirical broad-spectrum antibiotic therapy, prolonged vancomycin therapy, prolonged hospitalization, and immunosuppression. [3][4][5][6][7] From August through November 1993, 8 liver transplant recipients developed infections with VREF in our institution. While undertaking an epidemiology study, microbiological studies were also performed.…”
mentioning
confidence: 99%
“…Ten of 12 patients experienced VRE BSI during the neutropenic period (median 15 days post transplant, range [8][9][10][11][12][13][14][15][16][17][18][19][20][21], and mainly this occurred in patients with refractory or relapsed disease at the time of transplantation (70%). All VRE BSI patients were co-infected with other organisms including gram-negative bacilli, fungi or CMV, and five patients had intra-abdomial complications (GVHD, cholecystitis or typhlitis).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Up to 73% of enterococcal BSIs are due to vancomycin-resistant strains. 9 Risk factors for vancomycin-resistant enterococcal (VRE) colonization and infection include prolonged hospitalization, intensive care unit (ICU) stay, advanced age, immunocompromised state, neutropenia, high severity of underlying illness, antibiotic exposure, and indwelling urinary and vascular catheters, 8,[10][11][12][13] characteristics commonly found in patients on HSCT units. Several studies have investigated the significance of VRE infections in different patient populations and controversy exists as to whether VRE infections are associated with worse outcomes compared to vancomycin-sensitive enterococci.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in some US hospitals. 13,14 As seen in some other studies, microorganisms of HAI have more resistant profile than community acquired infection. 15 Majority of the isolated organisms were found sensitive to Tetracyclines and Chloramphenicol, which are not routinely prescribed these days.…”
Section: Discussionmentioning
confidence: 79%